Antiproliferative effect of growth hormone-releasing hormone (GHRH) antagonist on ovarian cancer cells through the EGFR-Akt pathway - Varga Jozsef; Zarandi Marta; Schally Andrew V; Guo Jian; Leung Peter CK (BMC, 2010)
Abstract Background Antagonists of growth hormone-releasing hormone (GHRH) are being developed for the treatment of various human cancers. Methods MTT assay was used to test the proliferation of SKOV3 and CaOV3. The splice variant expression of GHRH receptors was examined by RT-PCR. The expression of protein in signal pathway was examined by Western blotting. siRNA was used to block the effect of EGFR. Results In this study, we investigated the effects of a new GHRH antagonist JMR-132, in ovarian cancer cell lines SKOV3 and CaOV3 expressing splice variant (SV)1 of GHRH receptors. MTT assay showed that JMR-132 had strong antiproliferative effects on SKOV3 and CaOV3 cells in both a time-dependent and dose-dependent fashion. JMR-132 also induced the activation and increased cleaved caspase3 in a time- and dose-dependent manner in both cell lines. In addition, JMR-132 treatments decreased significantly the epidermal growth factor receptor (EGFR) level and the phosphorylation of Akt (p-Akt), suggesting that JMR-132 inhibits the EGFR-Akt pathway in ovarian cancer cells. More importantly, treatment of SKOV3 and CaOV3 cells with 100 nM JMR-132 attenuated proliferation and the antiapoptotic effect induced by EGF in both cell lines. After the knockdown of the expression of EGFR by siRNA, the antiproliferative effect of JMR-132 was abolished in SKOV3 and CaOV3 cells. Conclusions The present study demonstrates that the inhibitory effect of the GHRH antagonist JMR-132 on proliferation is due, in part, to an interference with the EGFR-Akt pathway in ovarian cancer cells.